TATA PAMERAN DAN KONSERVASI KOLEKSI DI GEDUNG BULELENG MUSEUM BALI - Nugraha Kertayasa, Dwi (Humanis; Volume 8. No. 3. September 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This study gives an overview of the exhibition layout and conservation collection Buleleng Building. Knowing that begins storyline of fabric types cerik langah, poleng fabric, endek fabric, splash fabric, grimace fabric, songket, and tinsel fabric. Collection of supporting materials such as cotton spinning collection into bennag feed, and cloth weaving process with cagcag loom. To maintain the quality of traditional woven cloth of Bali, conservation action is taken by two working methods that are traditionally and in a modern way. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: traditional woven fabric of Bali, arranging exhibition, and conservation Museum Bali.